Pencantuman Norma Akuntansi Enam Lima Serta Keterikatan Norma Akuntansi Satu Lima Dan Dua Dua Hal Susunan Gabungan - Yeremia Lie Yono; Danil Alfajri; Agus Kurniawan Dly; Ratih Kusumastuti (Pusat Riset dan Inovasi Nasional, 2023)
Arrangements for Complaints on the Stabilization Budget are regulated in Elucidation of the Principles of Monetary Bookkeeping (ACCOUNTING NORM) Number six five. Apart from the accounting norms number six five, there are two other accounting norms which also direct several views related to the Fiscal Consolidation plan, in particular, accounting norms number fifteen concerning representing interests in related organizations and accounting norms number two two concerning representing a mixture of businesses. ACCOUNTING NORM No. six five characterize the steps of the trade union and define the solidification methodology. Meanwhile, NORM ACCOUNTING No. One Five manages ventures that are properly represented using value techniques, which are closely related to United Reports. Then again, ACCOUNTING Rule No. dua dua regulates the accounting treatment for the business mix to take over in the form of bid procurement as well as net resources. This article examines the use of the three ACCOUNTING NORMs in preparing Solidified Fiscal complaints. The discussion began with a Business Blend Representation (ACCOUNTING NORM Number two two), followed by Speculation Bookkeeping with a Value Strategy (ACCOUNTING NORM Number One Five), finally discussing the United Report (ACCOUNTING NORM Number Six Five).